Factors Affecting The Gap Between Districts / Cities In North Maluku Province 2016-2020 - Muhammad Risal Johar (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this study is to analyze the effect of Economic Growth, Investment, agglomeration, on the regional disparities of districts/cities in North Maluku province in 2016-2020. The method of analysis used in this study is the regression of panel data for the period 2016-2020 sourced from the Central Bureau of Statistics of North Maluku. Statistical tests include Common, Fixed, and Random tests, as well as conducting Chow and Hausman tests to obtain the tests to be selected. The results of the data analysis showed that among the four economic growth variables (X1) has a negative and significant influence on the regional gap. Investment variables (X2) and agglomeration (X3) have a positive and significant influence on the regional gap.